(untitled) (Gaceta de Ciencias Veterinarias, 2017)
We analized 7096 ejaculates from Carora bulls of the Centre of Artificial Insemination Carora (CIAC, Venezuela). Of which, 2597 were discarded because they did not have minimal conditions for freezing. Other 1008 ejaculates were discarded post-thawing because not having at least 40% live sperm. Information about the moon cycle was obtained from the web site <http://aa.usno.navy.mil/data/docs/MoonFraction.php>. Based on the amount of moon luminosity seen during the 4 lunar phases (new moon or NM: 0%; first quarter or 1Q: 50%; full moon or FM: 100%; and third quarter or 3Q: 50%), the moon cycle has been divided into 4 stages: A (from FM to 3Q: 100-50% luminosity), B (3Q to NM: 50-0%), C (NM to 1Q: 0-50%), and D (1Q to FM: 50-100%). Data were processed using Statistix v 8.0 and analyzed using the Student’s “t” test for independent samples. There were significant (p<0.05) differences in the number of pre-freezing ejaculates discarded within stage A (100-50% luminosity), 86% being discarded in FM and 13% in 3Q. The number of post-thawing ejaculates discarded within stage D (50-100% luminosity) was also significantly (p<0.05) different, 85% being discarded in 1Q and 14,9% FM. There were no statistical differences in the number of pre-freezing or post-thawing ejaculates among the rest of the moon cycle stages. It is demonstrated an influence of lunar phases on Carora bull semen, which showed a higher quality during the decrescent stages (FM to 3Q) of the moon cycle.